Deficits in object-in-place but not relative recency performance in the APPswe/PS1dE9 mouse model of Alzheimer's disease: implications for object recognition - Bonardi, Charlotte; Pardon, Marie-Christine; Armstrong, Paul (Elsevier, 2016)
Performance was examined on three variants of the spontaneous object recognition (SOR) task, in 5-month old APPswe/PS1dE9 mice and wild-type littermate controls. A deficit was observed in an object-in-place (OIP) task, in which mice are preexposed to four different objects in specific locations, and then at test two of the objects swap locations (Experiment 2). Typically more exploration is seen of the objects which have switched location, which is taken as evidence of a retrieval-generated priming mechanism. However, no significant transgenic deficit was found in a relative recency (RR) task (Experiment 1), in which mice are exposed to two different objects in two separate sample phases, and then tested with both objects. Typically more exploration of the first presented object is observed, which is taken as evidence of a self-generated priming mechanism. Nor was there any impairment in the simplest variant, the spontaneous object recognition (SOR) task, in which mice are preexposed to one object and then tested with the familiar and a novel object. This was true regardless of whether the sample-test interval was 5 minutes (Experiment 1) or 24 hours (Experiments 1 and 2). It is argued that SOR performance depends on retrieval-generated priming as well as self-generated priming, and our preliminary evidence suggests that the retrieval-generated priming process is especially impaired in these young transgenic animals.